Offshore Assembly from the United States: Production Characteristics of the 9802 Program - Robert Feenstra; Gordon H. Hanson; Deborah Swenson (University of California, Department of Economics, 1998)
We study outsourcing from the United States under the offshore assembly program (OAP). Formerly called the 806/807 provision of the U.S. tariff code, and now renamed the 9802 provision of the Harmonized System code, this program allows U.S. firms to export component parts and have them assembled overseas. When the finished product is imported back into the United States, duties are paid only on the foreign value-added. We estimate the production characteristics of the U.S. OAP activity, and in particular, whether this activity is intensive in the use of non-production labor as compared to the overseas production. We also examine the sensitivity of OAP imports to real exchange rate movements.
Keywords: 330